2006
DOI: 10.1166/jnn.2006.484
|View full text |Cite
|
Sign up to set email alerts
|

Uptake and Biocompatibility of Functionalized Poly(vinylalcohol) Coated Superparamagnetic Maghemite Nanoparticles by Synoviocytes In Vitro

Abstract: Superparamagnetic iron oxide nanoparticles (SPION) were coated with either Polyvinyl alcohol (PVA) or Vinyl alcohol/vinyl amine copolymer and further functionalized with the fluorochromes Cy3.5 or Texas Red. A colloidally stable suspension of nanoparticles was incubated on sheep synovial cells in vitro for 3, 24, 72, and 120 hours. Nanoparticle internalization into synoviocytes as well as biocompatibility was visualized using light, fluorescence and confocal microscopy and fluorochrome labeled cells were quant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 0 publications
1
11
0
Order By: Relevance
“…Consistently, we previously showed that more than 80% of the synoviocytes took up superparamagnetic nanoparticles within 24 h [54]. These cells also showed the highest increase in transfection efficiency (8.8-fold) after the exposure to static magnetic field.…”
Section: Article In Presssupporting
confidence: 87%
See 1 more Smart Citation
“…Consistently, we previously showed that more than 80% of the synoviocytes took up superparamagnetic nanoparticles within 24 h [54]. These cells also showed the highest increase in transfection efficiency (8.8-fold) after the exposure to static magnetic field.…”
Section: Article In Presssupporting
confidence: 87%
“…Primary ovine synovial membrane cells (synoviocytes) were harvested and prepared for cell culture as previously described [54,55]. Briefly, synovial membranes of healthy sheep were collected under sterile conditions from the stifle joints immediately after slaughtering.…”
Section: Ovine Synoviocytesmentioning
confidence: 99%
“…Either the particles adhere to the periphery of the cell's plasma membrane, [37] or they are internalised. [38,39] After Prussian blue staining, the optical micrographs still clearly show the rather bulky nucleus, which tentatively suggests that internalisation occurred. Indeed, in case of a mere adhesion, one would expect the nucleus to be hidden under a uniform layer of Prussian blue stain, which evidently is not the case.…”
Section: Discussionmentioning
confidence: 88%
“…The hydroxyl groups (-OH) on the polymer skeleton ensure the hydrophobic property of the coating, which resembles the surface chemistry of carbohydrates such as dextran. The use of PVA-coated magnetic nanoparticles in biomedical applications has been reported (Schulze et al 2006). This research group has demonstrated the internalization of PVA and PVA co-polymer-coated magnetic nanoparticles by synoviocytes and by cells of the synovial membrane in sheep (Schulze et al 2005).…”
Section: Synthetic Organic Polymersmentioning
confidence: 99%